MAKNA SĪRŪ FĪ AL-ARḌ DALAM QS. AL-AN’AM [6]: 11 (Analisis Semiotika Roland Barthes) - Unzila, Alifia Rizqa; Balqis, Putroe (Jurnal Studi Islam dan Sosial, 2025)
This article examines the meaning of “sīrū fī al-arḍ” in surah al-An’ām [6]: 11, which is literally interpreted as a physical journey, as commonly undertaken by humans. However, because this command is mentioned several times in the Qur’an, which is rich with moral and spiritual messages, its meaning transcends mere physical activity. This study aims to uncover a deeper layer of meaning from this phrase through Roland Barthes semiotic analysis. Barthes analysis is carried out in two stages: the linguistic system, which explains the denotative meaning, and the mythology system, which explains the connotative meaning and the myth. This research uses a qualitative method with a literature review approach. The findings of the study show that the meaning of “sīrū fī al-arḍ” in its linguistic system is a command from Allah swt to humans to travel the earth. In the mythology stage, it is a command for humans to undertake a journey accompanied by reflection, both physically through traveling on earth and spiritually through reading and studying history. Through this connotative meaning, the myth meaning emerges: the importance of understanding history, whether acquired physically through direct travel or spiritually through deepening knowledge of history. This serves as a reminder that every action in this world will receive its reward. This is to prevent humans from being caught up solely in worldly pleasures.